Pengaruh sikap dan pengetahuan terhadap komitmen amalan standard halal: satu kajian dalam revolusi industri halal di Kota Kinabalu, Sabah - Nurul Hudani Md. Nawi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to explore the attitude and knowledge specifically the local halal industry towards the commitment for halal standard practice in Malaysia. Due to its importance, the second revised manual procedure for halal certificates (2011) has asserted that any halal industries that seek for halal certificate need to have an internal halal committee represented by various other units in the organization. The objective of the study is to determine the extent of attitude and knowledge influence the practice of halal commitment standard by the management in fulfilling the requirement of sharia compliance and the manual for certification procedure 2011 (second revision) (JAKIM, 2012) and Malaysian standard 1500: 2009 (Jabatan standard Malaysia, 2009). This study used cross-sectional survey method using questionnaire for the purpose of obtaining relevant information. The subject of the study consists of internal halal executive officer in Malaysia according to seven main scheme categories which are products, restaurant, tools, pharmaceutical product, slaughter-house, logistic, brushes, and bones. Data were analyzed using IBM SPSS statistics software version 24.0. The results of the study have shown that; i) Only aspects of attitude affect the practice of halal standard commitment (halal operation) and ii) attitude and knowledge influence the practice of halal standard commitment (halal guarantee).This study will be the basis for management authority in an organization to identify the attitude and leadership knowledge which are needed to influence the commitment for halal standard practice in an organization since they are the pioneers for ensuring the standard of an organization is achieved on the optimum level.